Utilization of Plants as Food Source: A Study in Sungai Bakah Village, Melawi Regency - Niconaus Niconaus; Hasan Ashari Oramahi; Fathul Yusro; Yeni Mariani (Jurnal Biologi Tropis, 2023)
Nature has a high potential for biological natural resources that humans, including plants as food, can utilize. This study aims to analyze the types of plants as a source of food used by the people of Sungai Bakah Village, Pinoh Selatan District, Melawi Regency. This study used a survey method. Respondents selected using a purposive sampling technique were interviewed to obtain data on the utilization of plants used as food ingredients. The data obtained is then analyzed using use value and fidelity level. The results showed that all respondents interviewed (131 respondents) used plants as a food source. A total of 84 types of plants were used, with fruit as the part that was most used (49.44%). Vegetables and fruits are the most widely used forms of utilization. Plants with the highest UV values ​​came from starch (Gymnopetalum cocinense), rice (Oryza sativa), chilies (Capsicum frutescens L.), and bamboo shoots (Dendrocalamus asper) with a value of 1. 84 plants species had the highest FL values ​​(100), most of which comes from the category of utilization as fruits.